karakteristik konsumen dan citra merek private label minimarket : perbandingan antara masyarakat desa dan masyarakat kota di kabupaten sleman - , Dini Pratiwi, Slamet Santoso Sarwono. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Private label is brand developed by retailer. Development of private label is followed by presence of development in retailer or modern store, mainly minimart easily to find. This study aimed to analyze a presence of difference in consumerâs characteristic and brand image of private label based on demographical and socio-economic between rural and urban people. The research was done by distributing questionnaire in District Depok located in village CondongCatur, Caturtunggal and Maguwo which categorized as urban and District Godean was categorized as village with location of gathering sample in Sidomoyo. Consumerâs characteristic of private label was measured by 12 variables of measurement consisted of four groups, including shopping/buying behavior on private label, reason to buy private label, attitude and level of involvement on private label. Number of sample used were 202 respondents consisted of 101 responde nts in rural and 101 respondents in urban. Result of the Anova and Post Hoc Test was presence of difference in rural and urban people based on consumerâs characteristic of private label, while from demographical and socio-economic segment, there was no difference between rural and urban people based on demographical status and the expense budget.